Intracaval and intracardiac extension of invasive thymoma complicated by superior and inferior vena cava syndrome. (25th December 2012) - Kurata, Atsushi; Saji, Hisashi; Ikeda, Norihiko; Kuroda, Masahiko
<x xml:space="preserve">Abstract</x> We present a case of an aged male with invasive thymoma that extended into the right atrium and led to superior and inferior vena cava syndrome. The patient initially presented with edema of the face and bilateral lower extremities. Echocardiography revealed a mass within the right atrium. Imaging studies demonstrated an anterior mediastinal tumor that continuously occupied the bilateral brachiocephalic veins, superior vena cava, and right atrium. Pathological diagnosis of the tumor biopsy was highly suspicious of thymoma. Due to the high risk of wide spread of the tumor, treatments including resection of the tumor were impossible. Several days later he died, and an autopsy was performed. The tumor was type B2 thymoma invading bilateral brachiocephalic veins, superior vena cava and right atrium. Multiple tumor emboli within the pulmonary arteries were identified. Direct cause of death was deemed to be tumor strangulation at the tricuspid orifice. In addition to the superior vena cava syndrome, inferior vena cava syndrome including ectasia of the intrahepatic vessels was confirmed along with pericarditis. To our knowledge, this is the first English report of an autopsy case of intracardiac thymoma extension, and a detailed literature review of similar cases is also presented.